2015
DOI: 10.1097/dad.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Skin Biopsy in the Diagnosis of Atypical Hemolytic Uremic Syndrome

Abstract: Introduction Atypical hemolytic uremic syndrome (aHUS) is a prototypic thrombotic microangiopathy attributable to complement dysregulation. In the absence of complement inhibition, progressive clinical deterioration occurs. We postulated that a biopsy of normal skin could corroborate the diagnosis of aHUS via the demonstration of vascular deposits of C5b-9. Materials and methods Biopsies of normal skin from 22 patients with and without aHUS were processed for routine light microscopy as well as immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 27 publications
1
33
0
1
Order By: Relevance
“…However, the majority of these patients are at high risk for bleeding complications following biopsy of the kidney. In a recent study, Magro et al 26 used skin biopsies to diagnose aHUS, and they found extensive microvascular depositions of C5b-9, which supported the diagnosis.…”
Section: Incidence Of Post-bmt Tmamentioning
confidence: 81%
“…However, the majority of these patients are at high risk for bleeding complications following biopsy of the kidney. In a recent study, Magro et al 26 used skin biopsies to diagnose aHUS, and they found extensive microvascular depositions of C5b-9, which supported the diagnosis.…”
Section: Incidence Of Post-bmt Tmamentioning
confidence: 81%
“…In our patient, a skin biopsy revealed C3 deposition on the vessel wall. Magro et al 9 reported that a skin biopsy is of value in establishing a diagnosis of TMA based on the microvascular deposition of complement in the dermis and subcutaneous fat. Because hypocomplementemia also existed in our patient, an alternative pathway of complement may have been associated with his TMA.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry for C9 or membrane attack complex deposition is possible in some laboratories, and can be performed on random skin biopsies. 4 It is worth noting that alternative complement activation occurs in other chronic conditions, such as diabetic vasculopathy, 5 so clinical correlation is required in interpreting results. Currently available serological testing is not helpful in this area.…”
Section: Routine Complement Blood Tests Are Insensitive For Alternatimentioning
confidence: 99%
“…Tests to support alternative pathway activation are those detecting activation and/or depositions of complement factors C5–C9. Immunohistochemistry for C9 or membrane attack complex deposition is possible in some laboratories, and can be performed on random skin biopsies . It is worth noting that alternative complement activation occurs in other chronic conditions, such as diabetic vasculopathy, so clinical correlation is required in interpreting results.…”
mentioning
confidence: 99%